Preoperative lactate, wound complications, and mortality following major amputation in patients with peripheral artery disease - Teguh Marfen Djajakusumah; Indra Prasetya Yarman; Azis Satrio Wibowo (Institute of Accounting Research and Novation (IARN), 2026)
Introduction: Peripheral Arterial Disease (PAD) is a leading cause of major lower-extremity amputation, particularly in patients with severe ischemia, gangrene, infection, or when revascularization is no longer feasible. Preoperative blood lactate is a biomarker reflecting tissue hypoperfusion and systemic metabolic stress, but its prognostic role in predicting postoperative wound complications and mortality after major amputation in PAD remains limited. Methods: This was an analytic observational study with a prospective cohort design conducted at Dr. Hasan Sadikin General Hospital between November 2024 and November 2025. Adult patients with PAD who underwent major amputation were enrolled using total sampling. Preoperative lactate levels were categorized into <2.5, 2.5–4, and >4 mmol/L, and associations with postoperative wound complications and mortality were analyzed using Fisher's Exact test. Results: A total of 51 patients met the study criteria; 60.8% were male and 52.9% were older than 60 years. Diabetes mellitus was the most common comorbidity (64.7%). Postoperative wound complications occurred in all patients with lactate >4 mmol/L, compared with 16 of 44 patients with lactate <2.5 mmol/L (p = 0.016). Mortality occurred in 4 of 5 patients with lactate >4 mmol/L, compared with 7 of 43 patients with lactate <2.5 mmol/L (p = 0.001). Discussion: Preoperative blood lactate is significantly associated with postoperative wound complications and mortality following major amputation in patients with PAD. Elevated lactate, particularly >4 mmol/L, identifies patients with worse postoperative outcomes, supporting its use as a simple, rapid, and accessible biomarker for perioperative risk stratification.